LESSON LEARN OF GEOCHEMISTRY OF HYDROCARBON GASES AND CO2 IN MESOZOIC PETROLEUM SYSTEM OF PAPUA NEW GUINEA: IMPLICATION FOR THE FOLD BELT PLAY CONCEPT IN EASTERN PAPUA, INDONESIA - Penggalih, Muhammad Saung; Subroto, Eddy Ariyono; Susanto, Very (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2024)
The potential of oil and gas discovery at the Fold Belt Play concept in eastern Papua could be learned from the multiple production fields in Papua New Guinea Fault and Thrust Belt area which has similar geological condition. Therefore, the geochemical characteristic of hydrocarbon gases and CO2 at the Fold Belt Play concept is expected to be predictable by the analogy of those gases occurrence in Mesozoic petroleum system of Papua New Guinea Fault and Thrust Belt area. The hydrocarbon gases are of thermogenic origin, generated from Type II/III kerogen of Jurassic-Cretaceous source rock with gas maturity of about 1.2 to 2.0% Ro equivalent. The average CO2 percentage in Mesozoic reservoir at Papua New Guinea is 1.58%. The relatively light d13C-CO2 (-25.2 to -10.4‰) unequivocally confirm that the low volume of CO2 is generated from kerogen maturation mechanism. For the Fold Belt Play concept in eastern Papua, the hydrocarbon gases are expected to have similar characteristic with the gases in Papua New Guinea. The low CO2 may probably only be found at Northern Fold Belt due to the preservation of thin-skinned deformation that have the basal detachment surface in the Kembelangan Group (Kopai Formation). On the other hand, the Central and Southern Fold Belt are predicted to contain moderate to high volume of inorganic CO2 migrated from Modio/Brug Dolomite. Key words: the Fold Belt Play, Mesozoic petroleum system, analogous, Papua New Guinea, eastern Papua